Reductive dechlorination of gamma-hexachlorocyclohexane using Fe-Pd bimetallic nanoparticles - Nagpal, Varima; Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Journal of Hazardous Materials, 2010)
Nanoscale Fe-Pd bimetallic particles were synthesized and used for degradation of lindane (gamma-hexachlorocyclohexane) in aqueous solution. Batch studies showed that 5 mg/Lof lindane was completely dechlorinated within 5 min at a catalyst loading of 0.5 g/L and the degradation process followed first-order kinetics. GC-MS analysis in corroboration with GC-ECD results showed the presence of cyclohexane as the final degradation product. The proposed mechanism for the reductive dechlorination of lindane involves Fe corrosion-induced hydrogen atom transfer from the Pd Surface. The enhanced degradation efficiency of Fe-Pd nanoparticles is attributed to: (1) high specific surface area of the nanoscale metal particles (60 m(2)/g), manyfold greater that of commercial grade micro- or milli-scale iron particles (similar to 1.6 m(2)/g); and, (2) increased catalytic reactivity due to the presence of I'd on the Surface. Recycling and column studies showed that these nanoparticles exhibit efficient and sustained catalytic activity. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Bimetallic; Cyclohexane; Degradation; kinetics; Lindane; Nanoparticles

Reply to comment on ``Reductive dechlorination of gamma-hexachlorocyclohexane using Fe-Pd bimetallic nanoparticles'', by C. Noubactep - Nagpal, Varima; Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Journal of Hazardous Materials, 2012)

Reductive cyclization of levulinic acid to gamma-valerolactone over non-noble bimetallic nanocomposite - Kadu, Brijesh S.; Hengne, Amol M.; Biradar, Narayan S.; Rode, Chandrashekhar V.; Chikate, Rajeev C. (Industrial & Engineering Chemistry Research, 2016)
Bimetallic nanoparticles have diverse applications in catalytic processes owing to the differences in individual properties that contribute to their increased catalytic activity. To further improve the efficiency, they are dispersed in an inert support that enhances the catalytic activity toward organic transformations. In this study, we report simple, facile, and cost-effective chemical route for the fabrication of nanocomposites with Fe-Ni bimetallic nanoparticles supported on montmorillonite (MMT) possessing variation in the Fe and Ni content. These composites are characterized with X-ray diffraction, transmission electron microscopy surface area, and NH3-TPD. Fe Ni bimetallic nanoparticles are well-dispersed within MMT structure having particle sizes of about 30-40 nm. Among various compositions of Fe-Ni/MMT catalysts, composite with 25% Fe and 25% Ni exhibits >99% LA conversion with 98% selectivity to GVL within 1 h. IPA is found to be better solvent for levulinic acid (LA) to gamma-valerolactone (GVL) conversion, while substantial leaching of iron takes place when water is used as a solvent. It is observed that bimetallic sites are responsible for reduction of LA, while strong acidic sites of MMT are favoring subsequent cyclization to GVL. XPS analysis of fresh and reused Fe-Ni/MMT composites suggest that the catalyst surface does not undergo any chemical change during successive cycles, and the catalytic activity is retained up to six cycles. The plausible mechanism for LA to GVL conversion involves reductive cyclization processes through formation of levulinate ester that undergoes lactonization due to synergism in bimetallic nanoparticles and MMT clay.